(untitled) (CIPEEX, 2026)
Brazilian education has been a topic of debate for decades. Much is said about the best teaching approaches, the use of specific learning techniques, and the state’s intervention or non-intervention. Taking this debate as a starting point, this research reflects on public education in Brazil, addressing the state’s regulatory role and analyzing the benefits and drawbacks of its role in the education sector. It is noteworthy that the right to education is guided primarily by the Federal Constitution and the Law of Guidelines and Bases for National Education (LDB), standards that govern the rights and duties of educators and students, in addition to consolidating education as a fundamental right. The study also points out that alternative teaching models, different from those desired by the state, can be effective. In this context, the essential role of the family as a complementary agent in educational development is emphasized, contributing significantly to the development of a quality education.